ЗАТТАРДЫ КЕДЕН БАҚЫЛАУЫНАН ЖАСЫРЫП ҚАЛУ АРҚЫЛЫ ЭКОНОМИКАЛЫҚ КОНТРАБАНДА ЖҮЗЕГЕ АСЫРУ ПРОБЛЕМАЛАРЫ (Journal of actual problems of jurisprudence, 2019)
In article problems not lawful transportation through customs posts of things and value are considered. Problems of a fake ofdocumentation for transfer are considered.